Holocene transgression and sea level change offshore Peninsular Malaysia (innermost Sunda Shelf) as indicated by benthic foraminiferal, lithologic and geochronologic data. (10th March 2023) - Suriadi, Rokiah; Shaari, Hasrizal; Culver, Stephen J.; Sulaiman, Abdullah; Yang, Shouye; Saelan, Wan Nurzalia Wan; Minhat, Fatin Izzati; Sharif, Hamad Maalim
Abstract: The history of Holocene sedimentation on the Sunda Shelf (southern South China Sea), one of the largest shelves in the world, has received little attention, particularly off Peninsular Malaysia. We present here evidence of Holocene transgression from most of the inner shelf of Peninsular Malaysia, based on lithologic and foraminiferal analyses of 24 cores from 13.5 m to 46.8 m water depth encompassing the coastal sand wedge and the immediately adjacent shelf. Six benthic foraminifera biofacies occur within these cores and, together with lithologic data and five AMS radiocarbon age estimates, enable recognition of three units previously defined in cores taken from 52 m to 77 m water depth. Eleven of 24 cores contain Unit 3, earliest Holocene coastal plain semi-consolidated peaty, sandy clay deposits that represent the lowest part of the post-last glacial maximum transgressive systems tract (TST). In a single core, Unit 4 open marine, inner shelf sandy mud deposits of the early Holocene upper part of the TST overlie Unit 3. In 23 cores Unit 3 is directly overlain by Unit 5, open marine, inner shelf sandy mud deposits of the highstand systems tract (HST) and laterally equivalent sediments within the coastal sand wedge that accumulated after the mid-Holocene sea-level maximum.